Metabolite identification using an ion mobility enhanced data‐independent acquisition strategy and automated data processing. (11th May 2020) - Radchenko, Tatiana; Kochansky, Christopher J.; Cancilla, Mark; Wrona, Mark D.; Mortishire‐Smith, Russell J.; Kirk, Jayne; Murray, Gordon; Fontaine, Fabien; Zamora, Ismael
Abstract : Rationale: Liquid chromatography/mass spectrometry is an essential tool for efficient and reliable quantitative and qualitative analysis and underpins much of contemporary drug metabolism and pharmacokinetics. Data‐independent acquisition methods such as MS E have reduced the potential to miss metabolites, but do not formally generate quadrupole‐resolved product ion spectra. The addition of ion mobility separation to these approaches, for example, in High‐Definition MS E (HDMS E ) has the potential to reduce the time needed to set up an experiment and maximize the chance that all metabolites present can be resolved and characterized. We compared High‐Definition Data‐Dependent Acquisition (HD‐DDA), MS E and HDMS E approaches using automated software processing with Mass‐MetaSite and WebMetabase. Methods: Metabolite identification was performed on incubations of glucagon‐like peptide‐1 (7‐37) (GLP‐1) and verapamil hydrochloride. The HD‐DDA, MS E and HDMS E experiments were conducted on a Waters ACQUITY UPLC I‐Class LC system with a VION IMS quadrupole time‐of‐flight (QTOF) mass spectrometer operating under UNIFI control. All acquired data were processed using MassMetaSite able to read data from UNIFI 1.9.4. WebMetabase was used to review the detected chromatographic peaks and the spectral data interpretations. Results: A comparison of outcomes obtained for MS E and HDMS E data demonstrated that the same structures were proposed for metabolites of both verapamil and GLP‐1. The ratio of structurally matched to mismatched product ions found by MassMetaSite was slightly greater for HDMS E than for MS E, and HD‐DDA, thus improving confidence in the structures proposed through the addition of ion mobility based data acquisitions. Conclusions: HDMS E data acquisition is an effective approach for the elucidation of metabolite structures for both small molecules and peptides, with excellent accuracy and quality, requiring minimal tailoring for the compound under investigation.